(untitled) (Journal of Atomic and Molecular Sciences, 2012)
Based on the specific microstructure of HDDR (hydrogenation, disproportionation, desorption, recombination) grains, that the bivariate model concerning the anisotropy constant K'_1 and exchange integral A'_1 in defect region, which was put forward. Subsequently, the dependence of magnet coercivity on the intergranular phase thickness d and structure defect thickness r_0 was studied. The results showed that the coercivity, H_c, increases with increasing d, for the r_0, the anisotropy constant K_1(0) and exchange integral constant A_1(0) at the grain surface taking different values. While K_1(0) and A_1(0) are fixed, H_c enhances with increasing r_0 for the same d. On the contrary, for the fixed r_0 and d, H_c decreases with increasing K_1(0) or A_1(0). The calculated coercivity is in good agreement with experimental results given by others when d takes 1 nm, r_0 is in the rang of 2-5 nm, A_1(0) and K_1(0) change in the range of (0.6-0.7) of A_1 and K_1, respectively.